The Temperature Dependence of Photoconductivity in a-Ge20Se80 Thin Films - Abbas, Nada K. (Iraqi Journal of Physics, 2008)
The photoconductivity and its dependence on light intensity have been investigated in a-Ge20Se80 thin films as a function of temperature between (293–323)K. The result showed that the photoconductivity and photosensitivity increase with increase of annealing temperature. This behavior is interpreted in terms of the dispersive diffusion –controlled recombination of localized electrons and holes.